Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
Digital Technology in Physical Education 2018
DOI: 10.4324/9780203704011-5
|View full text |Cite
|
Sign up to set email alerts
|

Exploring pedagogies of digital technology in physical education through appreciative inquiry

Abstract: From a pedagogical perspective, what physical education (PE) teachers think, say and do with regards to digital technology has received little attention (Lupton 2015). This chapter examines a case study of 'Patrick', a UK PE teacher who embedded digital technology into his teaching. Using a case study approach guided by appreciative inquiry, this chapter draws on the views and experiences of Patrick, and others in his school, regarding digital technology use in an effort to understand the factors and experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
2
0
1
Order By: Relevance
“…This condition is well documented in the literature on preservice teachers (Fuller & Manning, 1973). The effectiveness of self-video feedback depends on its ability to show preservice teachers the effects of teaching on student behavior (Sargent, 2018). It also depends on the ability of this type of device to link these effects to the specifics of the subject being taught and to what teachers know about adapting pedagogical content to transform students' behavior (Carter, 1990).…”
Section: Use Of Digital Tablets For Stc Education In Team Sportsmentioning
confidence: 95%
“…This condition is well documented in the literature on preservice teachers (Fuller & Manning, 1973). The effectiveness of self-video feedback depends on its ability to show preservice teachers the effects of teaching on student behavior (Sargent, 2018). It also depends on the ability of this type of device to link these effects to the specifics of the subject being taught and to what teachers know about adapting pedagogical content to transform students' behavior (Carter, 1990).…”
Section: Use Of Digital Tablets For Stc Education In Team Sportsmentioning
confidence: 95%
“…Indeed, the main findings on technology-based interventions, including online and blended, in physical education, found that the use of technology was mainly focused to enhance health or motivational variables, but not curriculum learning outcomes (Killian et al, 2019;Sargent & Calderón, 2021). As Sargent and Casey (2019) reported, some types of digital technology used in physical education classes include iPads, Exergaming (Meckbach et al, 2013), Wii Fit Plus (Almqvist et al, 2016), apps and social media (Casey et al, 2017), video projectors and heart rate monitors (Thomas & Stratton, 2006). Student motivation is a key characteristic in the implementation of digital technology.…”
Section: Digital Technology For Teaching and Learning In Physical Edu...mentioning
confidence: 99%
“…Use to create user friendly resources tailored to the lesson content Strengths Weaknesses (Armour et al, 2017. Padlet (online) (Sargent and Casey, 2018).…”
Section: Strengths Weaknessesmentioning
confidence: 99%
“…Online message board where users can post notes and have discussions on a virtual message wall (Sargent and Casey, 2018).…”
Section: Strengths Weaknessesmentioning
confidence: 99%